2005
DOI: 10.1038/sj.ejcn.1602307
|View full text |Cite
|
Sign up to set email alerts
|

Intake of milk fat, reflected in adipose tissue fatty acids and risk of myocardial infarction: a case–control study

Abstract: Objective: To study the association between content of fatty acids from milk fat (14:0, 15:0 and 17:0) in adipose tissue and risk of a first myocardial infarction (MI). Design and subjects: A case-control study with 99 patients and 98 population controls both men and postmenopausal women, age 45-75 year. Adipose tissue fatty acids were determined by gas-liquid chromatography. Results: The content of 14:0, 14:1, 15:0, 17:0 and 17:1 were all significantly higher in adipose tissue of controls than of the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 42 publications
3
35
0
9
Order By: Relevance
“…The correlations were weaker when food intake was assessed by food frequency questionnaire (FFQ) compared with repeated food records [5]. Notably, dairy intake was more strongly correlated with adipose 15 : 0 than 17 : 0 [5,6,10,11], showing a clear dose–response relationships between intake and 15 : 0 [11]. In adipose tissue, the mean or median proportions of 15 : 0 range from 0.19 (Costa Rica) to 0.39 (Norway) and for 17 : 0 from 0.21 to 0.34 [5,6,10,1214].…”
Section: Biomarkers Of Dairy Intake: Observational Studiesmentioning
confidence: 99%
“…The correlations were weaker when food intake was assessed by food frequency questionnaire (FFQ) compared with repeated food records [5]. Notably, dairy intake was more strongly correlated with adipose 15 : 0 than 17 : 0 [5,6,10,11], showing a clear dose–response relationships between intake and 15 : 0 [11]. In adipose tissue, the mean or median proportions of 15 : 0 range from 0.19 (Costa Rica) to 0.39 (Norway) and for 17 : 0 from 0.21 to 0.34 [5,6,10,1214].…”
Section: Biomarkers Of Dairy Intake: Observational Studiesmentioning
confidence: 99%
“…Use of biological markers may represent a more accurate measure of intake than FFQ, and our previously reported results showed that the OR for MI were significantly reduced with increasing quartiles of 15:0 in adipose tissue even after adjustment for lifestyle factors (Biong et al 2006). This suggests that the intake of dairy fat or some other component of dairy products, as reflected by C15:0 as a marker in adipose tissue, may possibly protect persons at increased risk from having a first MI.…”
Section: Discussionmentioning
confidence: 73%
“…Previously, Biong et al (2006) have used these data to show that intake of dairy fat or some other component of dairy products, as reflected by C15:0 as a marker in adipose tissue, is associated with reduced risk of myocardial infarction (MI). In the present analyses the same data have been used to assess whether this reduced MI risk may be reflected in the self-reported intake of different food items (food frequency questionnaire [FFQ]), in particular different dairy products*and, if so, what kind of dairy products.…”
Section: Introductionmentioning
confidence: 98%
“…Two Swedish studies have shown that cardiovascular risk factors were negatively associated with intake of milk fat [42,43]. A Norwegian study suggests that intake of dairy fat or some other component of dairy products, as reflected by C15:0 as marker in adipose tissue may protect persons at increased risk from having a first myocardial infarction (MI), and that the causal effects may rely on other factors than serum cholesterol [44]. It has been shown that 34 grams dairy fat per day gives no negative effect on odds ratio for myocardial infarction [45].…”
Section: Saturated Fatty Acidsmentioning
confidence: 97%
“…Accordingly milk and milk products contribute substantially to the dietary intake of oleic acid in many countries. In Norway about a quarter of the average intake of oleic acid comes from milk and milk products [40][41][42][43][44][45][46]. Oleic acid is considered to be favourable for health, as diets with high amounts of monounsaturated fatty acid will lower both plasma cholesterol, LDL-cholesterol and triacylglycerol concentrations [48], and replacement of saturated fatty acids with cis-unsaturated fatty acids reduces risk for coronary artery disease [24].…”
Section: Unsaturated Fatty Acidsmentioning
confidence: 99%